Critical review of the interdisciplinary approach of the book «Comprehensive Dentistry: contemporary challenges in oral care» - Guillén, Ximena S. (Revista Gregoriana de Ciencias de la Salud, 2025)
This critical review analyzes the interdisciplinary approach of the book Comprehensive Dentistry: contemporary challenges in oral care, compiled by Santos and Galarza (2024). The book is organized into eight thematic chapters that address key areas of modern dental practice, including care for vulnerable populations (children with Down syndrome, individuals with disabilities, and older adults) and advanced clinical techniques (fiberglass post rehabilitation, conservative pulp therapy, space maintenance, and treatment of ameloblastoma). Each chapter, based on research conducted at San Gregorio de Portoviejo University, provides an up-to-date, contextually grounded, and academically rigorous perspective, complete with practical recommendations and recent references. The book stands out as a pedagogical and continuing education resource, facilitating the application of scientific knowledge to clinical practice and promoting patient-centered, evidence-based, and equitable dentistry. Its clear structure and multidisciplinary scope make it a valuable reference for students, educators, and dental professionals alike.